Persepsi Masyarakat Tentang Risiko Penyakit Terhadap Kesiapsiagaan Bencana Banjir Di Kecamatan Cabangbungin Kabupaten Bekasi - Rismawati Pangestika; Ikhwan Ridha Wilti; Ana Utami Zainal; Siti Dahlia (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
One of the flood-prone sub-districts in Bekasi Regency, namely Cabungbungin District, which since 2018-2020 has experienced an increase in the number of areas experiencing flooding, so an analysis of community preparedness in dealing with floods is needed. The purpose of this study is to determine the relationship between perceptions of flood risk, experience of flood disasters in a year, and health knowledge about flood-related diseases on community preparedness actions as an effort to mitigate flood disasters. This research is a quantitative study with a cross sectional design with sampling using purposive sampling technique on 100 respondents. Data were analyzed univariately and bivariately using Chi-square to see the relationship between variables of perception, knowledge, and experience on flood disaster preparedness actions. The results showed that the experience of flooding in the last 1 year and the public's perception of flood risk showed no statistically significant relationship with preparedness actions to face flood disasters (p=0.629 and p=0.295). Meanwhile, the variable of public knowledge about flood disease shows that there is a statistically significant relationship with flood preparedness actions with a value of OR = 4.20 (95% CI: 1.676-10,645 ; p = 0.001). This value shows that people who have low knowledge about flood diseases tend to have 4 times the risk of being less prepared in terms of preparedness for flood disasters.